Foresight online economic modelling training course - McCluskey, Alyssa; Schuetz, Tonya (2024)
The Foresight Initiative invested in the development of an Online Economic Modeling Training Course. This led to the design of a modular online training course with seven modules. These seven modules cover introducƟon to models and economic modeling, and two separate tracks for mulƟ-market modeling with parƟal equilibrium (PE) models and computable general equilibrium (CGE) models and modeling.